Effects of varying ion flux on high vacuum evaporated erbium thin films. (July 2019) - Banerjee, A.; Umapathy, G.R.; Abhilash, S.R.; Ojha, S.; Unnati,; Kabiraj, D.; Mandal, S.
Abstract: For the first time, to the best of our knowledge, a comprehensive study has been carried out to investigate the effects of ion beam on erbium thin films. Thin enriched erbium films with areal density ∼50–200 μg/cm 2 sandwiched between carbon films were prepared using the high vacuum deposition technique. The samples were bombarded with fluorine ion beam accelerated to 90 MeV energy using a tandem accelerator. Irradiation time was varied for each sample. Accelerator based characterization technique-Rutherford Backscattered Spectrometry (RBS) was used to study the structural changes induced by ion beam irradiation. The morphology and composition of the samples were studied using Field Emission Scanning Electron Microscopy (FE-SEM) and Energy Dispersive x-ray Spectroscopy (EDS), respectively. Comparisons have been drawn between the various samples and with pristine erbium sample. These results show that erbium films are quite stable under energetic ion beam irradiation. This makes their application in various fields dealing with high radiation protection and shielding possible.